2020
DOI: 10.18231/2581-4222.2018.0029
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of pulmonary function tests among the municipal street sweepers of Chitradurga District, Karnataka

Abstract: Municipal street sweepers are exposed to large amount of dusts, microorganisms, toxins and automobile exhaust pollution. Chronic inhalation of such particulate matter has the potential to impair their pulmonary functions. The strict adherence to the standards and norms for the management of municipal solid wastes to reduce occupational health hazards in developing countries India is still a matter of concern. This study conducted among the municipal sweepers of Chitradurga district, compared the effects of chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Other authors also reported a negative correlation between the duration of exposure and lung function values for street sweepers [12,[27][28][29]. In most of the recent studies, the results of lung function measurements were adjusted for smoking [24,28] or the comparison with control subjects was only performed in non-smoking subjects [23,25,29]. Most of these studies showed that the decline of lung function was aggravated in smoking individuals.…”
Section: Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors also reported a negative correlation between the duration of exposure and lung function values for street sweepers [12,[27][28][29]. In most of the recent studies, the results of lung function measurements were adjusted for smoking [24,28] or the comparison with control subjects was only performed in non-smoking subjects [23,25,29]. Most of these studies showed that the decline of lung function was aggravated in smoking individuals.…”
Section: Infectionsmentioning
confidence: 99%
“…A number of studies have revealed that street sweepers, especially in emerging and developing countries, are at risk of infectious diseases as they are exposed to inhalable matter, microorganisms, injuries, cuts and wounds. While a Kenyan study found that the involved street cleaners had little knowledge about the possible ways of transmitting infections and diseases [13], interviews with 70 street sweepers and garbage collectors from Egypt showed that between street cleaners and control subjects [23][24][25], indicating an obstructive pattern. Additionally, Sani et al [24] discussed that, due to the significant decline in forced expiratory flow (FEF 25-75 ) and peak expiratory flow (PEF), dust exposure of street sweepers might cause obstructive changes also in the small airways.…”
Section: Infectionsmentioning
confidence: 99%